Highly dispersed nanoparticles and dispersion method thereof and particle-reinforced metal matrix composite materials

By utilizing the shear stress of the concave and convex structure and the binder in the double helix extrusion device, high dispersion of nanoparticles is achieved, the problems of uneven dispersion and agglomeration are solved, and the strength and elongation of the metal-based composite material are improved.

CN116174706BActive Publication Date: 2024-12-13GUANGDONG INST OF NEW MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310201480.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-03
Publication Date
2024-12-13
Estimated Expiration
2043-03-03

AI Technical Summary

Technical Problem

In the prior art, nanoparticles are dispersed unevenly and agglomerated over time, resulting in worse interface bonding, stress concentration and material strength decrease.

Method used

The first coated nanoparticles and the second particles are mixed and dispersed under an inert atmosphere by using a double helix extrusion device. The coating film is softened and evenly coated by using the adhesive and shear stress on the spiral surface of the concave and convex structure. On the surface of nanoparticles, electrostatic attraction is eliminated and high dispersion is achieved.

Benefits of technology

The uniform dispersion of nanoparticles is achieved, the tensile strength, yield strength and elongation of the material are enhanced, the agglomeration phenomenon is avoided, and the long-term stability of the composite material and the feasibility of multiple uses are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116174706B_ABST
    Figure CN116174706B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of material processing, and specifically relates to highly dispersed nanoparticles and a dispersion method thereof and a particle-reinforced metal-based composite material. The dispersion method comprises: in a double-screw extruder, in an inert atmosphere, mixing and dispersing a first coated nanoparticle and a second particle; the first coated nanoparticle comprises a first nanoparticle and a coating film coated on the surface of the first nanoparticle; wherein the size of the first nanoparticle is smaller than the size of the second particle; the temperature of the mixed dispersion causes the coating film to soften and have viscosity; the double-screw extruder has a spiral surface, a concave-convex structure is arranged on the spiral surface, and the concave-convex structure satisfies: the concave-convex projection D is 0.1-0.5mm, and the concave-convex height difference H is 250-600nm. The present invention can eliminate the electrostatic attraction between the first nanoparticles in the mixed dispersion, so that the nanoparticles are evenly dispersed inside and can be stored for a long time without agglomeration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material processing, and in particular relates to highly dispersed nanoparticles and a dispersion method thereof, and particle-reinforced metal-based composite materials. Background Art

[0002] Nanoparticles have been successfully used in many fields, including medicine, pharmacy, chemical and biological detection, manufacturing, optics and national defense. In recent years, nanoparticles are often used to prepare composite materials, coatings, etc. No matter what application of nanoparticles, the problem of nanoparticle dispersion is involved, which is also a difficult problem to solve at present. A number of studies have been conducted in the prior art.

[0003] CN111961904A discloses a method for preparing a nano-ceramic phase reinforced metal matrix composite material, which uses metal material as the matrix and ceramic particles as the reinforcement phase. 2 , WC and A1 2 O 3 One or more ceramic particles in the raw material are used as raw materials, and the mass percentage of ceramic particles added is 1.0-5.0%. A metal-based composite powder with uniform distribution of nano-ceramics is prepared by a specific ball milling process, and a metal-based composite material with nano-ceramic phase is prepared by 3D printing technology. The prepared metal-based composite material has uniform distribution of nano-ceramic phase and excellent mechanical properties. The use of micron-level ceramic particles is low in cost; parts of any complex shape can be prepared in one piece, thereby improving material utilization.

[0004] CN112846198A discloses a nanoparticle-reinforced metal-based composite material and a preparation method thereof. The method is as follows: firstly, the nanoparticles are surface modified and pre-dispersed to make them in a relatively dispersed state before ball milling; then, the materials are fully mixed by low-speed ball milling in the initial stage of ball milling; in the middle stage of ball milling, the metal powder is flaked and the nanoparticle embedding mechanism is combined, and the process hardening phenomenon of the flaky metal powder is improved and eliminated by stress relief annealing, so as to solve the problem of nanoparticles being de-embedded on the surface of the flaky metal powder and the problem of low load; finally, the rotation speed is reduced, and the flaky powder with a relatively large diameter-thickness ratio is mechanically crushed by grinding balls, and then fine flaky nanoparticle-reinforced metal-based composite material powder is obtained by pressing, sintering and densification. The present invention effectively solves the problem of metal powder process hardening by surface modification, pre-dispersion treatment and stress relief annealing in the ball milling process, so that the nanoparticles are more evenly dispersed and have a higher load.

[0005] However, many methods for dispersing nanoparticles, such as ball milling, ultrasonic method, melt stirring method, chemical method, etc., have achieved certain effects, but there is still uneven dispersion in the macro / micro range, especially as time goes by, the dispersed particles will regroup. Unevenly dispersed nanoparticles will regroup at the interface between the matrix and the reinforcing particles, making the interface bonding worse. When the load is applied, it cannot be effectively transmitted, resulting in stress concentration and fracture, and a significant decrease in strength and plasticity. Summary of the invention

[0006] The purpose of the present invention is to overcome the defect of the prior art that nanoparticles are difficult to disperse, and to provide highly dispersed nanoparticles and a dispersion method thereof and a particle-reinforced metal-based composite material. In the highly dispersed nanoparticles, first coated nanoparticles are distributed on the surface of second particles, and the first nanoparticles distributed on the surface of the second particles do not contact each other. The highly dispersed nanoparticles can be applied to multiple industrial fields such as particle-reinforced composite materials.

[0007] In order to achieve the above object, in a first aspect, the present invention provides a method for dispersing nanoparticles, comprising: in a double-screw extruder, under an inert atmosphere, mixing and dispersing first coated nanoparticles and second particles; the first coated nanoparticles comprising first nanoparticles and a coating film coated on the surface of the first nanoparticles;

[0008] wherein the size of the first nanoparticle is smaller than the size of the second nanoparticle;

[0009] The temperature of the mixed dispersion causes the coating film to soften and become viscous;

[0010] The double-screw extruder has a spiral surface, and a concave-convex structure is arranged on the spiral surface, and the concave-convex structure satisfies: the concave-convex projection D is 0.1-0.5mm, and the concave-convex height difference H is 250-600nm. The concave-convex projection D refers to the projection distance of any convex part or any concave part in the concave-convex structure on the spiral surface under the irradiation of light perpendicular to the spiral surface, and the concave-convex height difference H refers to the distance between the highest point of any convex part and the lowest point of any concave part in the irradiation direction of light perpendicular to the spiral surface.

[0011] In some preferred embodiments, the size of the second particles is micrometer-sized.

[0012] In some preferred embodiments, the particle size distribution range of the second particles is 1-1000 μm.

[0013] In some preferred embodiments, the volume percentage of the second particles in the total amount of the first nanoparticles and the second particles is 50%-99%; the volume percentage of the coating film in the total amount of the first nanoparticles and the second particles is 10%-80%, preferably 25%-60%. This preferred solution is more conducive to the coating film completely coating the surface of the first nanoparticle, and at the same time, it is conducive to the first nanoparticles being evenly dispersed on the surface of the second particles without contacting each other.

[0014] In some preferred embodiments, the first nanoparticles include at least one of metal nanoparticles and inorganic non-metallic nanoparticles.

[0015] In some preferred embodiments, the second particles include at least one of metal particles and inorganic non-metal particles.

[0016] In some preferred embodiments, the coating film is a binder layer, including at least one of stearic acid, resin, and polyvinyl alcohol.

[0017] In some preferred embodiments, the mixing and dispersing temperature is 10-500°C, preferably 250-500°C.

[0018] In some preferred embodiments, the mixing and dispersing time is 10-200 min.

[0019] In some preferred embodiments, the dispersion method further comprises the step of forming the first coated nanoparticles:

[0020] (1) In an inert atmosphere, a binder for forming a coating film is introduced into the twin-screw extruder for operation, so that the binder adheres to the surface of the concave-convex structure;

[0021] (2) Introducing the first nanoparticles into the double-screw extruder of step (1) for mixing and coating under an inert atmosphere.

[0022] More preferably, the operating conditions include: temperature of 10-500° C. and time of 10-120 min.

[0023] More preferably, the mixed coating conditions include: temperature of 100-500° C. and time of 10-200 min.

[0024] In a second aspect, the present invention provides highly dispersed nanoparticles, which are prepared by the dispersion method described in the first aspect.

[0025] In a third aspect, the present invention provides a particle-reinforced metal matrix composite material, which comprises the highly dispersed nanoparticles described in the second aspect, and an alloy; the properties of the particle-reinforced metal matrix composite material meet the following requirements: tensile strength higher than 260 MPa, yield strength higher than 200 MPa, and elongation higher than 3%.

[0026] Preferably, the tensile strength is higher than 350 MPa, the yield strength is higher than 300 MPa, and the elongation is higher than 10%.

[0027] The present invention disperses first coated nanoparticles formed by coated first nanoparticles and second particles of relatively larger size by using a double-screw extruder with a special concave-convex structure. On the one hand, the double-screw extruder with the concave-convex structure is used to disperse large and small particles, which is more conducive to significantly improving the dispersion performance. The concave-convex structure makes the surface of the spiral surface have a suitable roughness. Under the friction force generated by the rough surface and the effects of shear stress, rolling, extrusion, rolling, etc., the first coated nanoparticles are squeezed and adhered to the surface of the second particle (large particle) and are evenly dispersed, so that the first nanoparticles do not contact each other. The concave-convex projection D is 0.1-0.5 mm. The height difference H of the concave and convex is 250-600nm, which can ensure that the surface coating film of the first nanoparticle can be evenly and completely coated on the surface of the first nanoparticle, ensuring that the first nanoparticles do not contact each other, and at the same time, the first nanoparticles and the surface coating film can be evenly and completely coated on the surface of the second particle; on the other hand, the first coated nanoparticles are specially used, and the coating film thereon is coated on the surface of the first nanoparticles. Compared with the traditional method of directly mixing the two particles, the electrostatic attraction between the first nanoparticles in the mixed dispersion can be eliminated, so that the first nanoparticles are dispersed more evenly on the surface of the second particles; the synergy of the above two aspects makes the nanoparticles evenly dispersed inside and preserved for a long time without agglomeration.

[0028] In the preferred scheme of using a double-screw extruder to prepare the first coated nanoparticles, since the spiral surface of the double-screw extruder is provided with a concave-convex structure and has a suitable roughness and a specific rough structure, the binder adheres to the spiral surface during the spiral operation. In the subsequent operation of the double-screw extruder after the first nanoparticles are introduced, the spiral surface produces rolling, extrusion, tumbling, shearing and other effects on the first nanoparticles, so that the binder is forced into the first nanoparticles and separates the first nanoparticles. At the same time, due to the rolling, extrusion, tumbling, shearing and other effects, the surface of the first nanoparticles is coated with a layer of binder, which is more conducive to the high dispersion of the first nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0030] Figure 1 It is a schematic structural diagram of the helicoid of the present invention.

[0031] Figure 2 This is the dispersion morphology of the nano-titanium particles in the micron magnesium particles of Example 1 of the present invention.

[0032] Figure 3 This is the dispersion morphology of the nano-titanium particles on the micron magnesium particles in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0034] In a first aspect, the present invention provides a method for dispersing nanoparticles, comprising: in a twin-screw extruder, under an inert atmosphere, mixing and dispersing first coated nanoparticles and second particles; the first coated nanoparticles include first nanoparticles and a coating film coated on the surface of the first nanoparticles.

[0035] Wherein, the size of the first nanoparticles is smaller than that of the second nanoparticles.

[0036] Among them, the double-screw extruder has a spiral surface, and a concave-convex structure is arranged on the spiral surface, and the concave-convex structure satisfies: the concave-convex projection D is 0.1-0.5mm, and the concave-convex height difference H is 250-600nm. The concave-convex projection D refers to the projection distance of any convex part or any concave part in the concave-convex structure on the spiral surface under the irradiation of light perpendicular to the spiral surface, and the concave-convex height difference H refers to the distance between the highest point of any convex part and the lowest point of any concave part in the direction of light irradiation perpendicular to the spiral surface.

[0037] The concave-convex projection D is 0.1-0.5 mm, specifically 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 mm; the concave-convex height difference H is 250-600 nm, specifically 250, 300, 350, 400, 450, 500, 550, 600 nm.

[0038] The concave-convex projection D and the concave-convex height difference H of the present invention are as follows: Figure 1 As shown, the direction of light irradiation is Figure 1 It is shown in FIG. 1 , and it should be understood that, since it is a helical surface, there are multiple vertical light irradiation directions of the helical surface, as long as the projection distance or the concave-convex height difference H under the vertical light irradiation direction of any part of the helical surface is respectively within the above range, preferably, the projection distance (i.e., any distance on the projection of the helical surface) or the concave-convex height difference H under all vertical light irradiation directions perpendicular to the helical surface are respectively within the above range. Those skilled in the art can select the average value of the projection distance or the concave-convex height difference H under the condition of satisfying the above range, preferably, the average value of the concave-convex projection D is 0.15-0.4mm, and the average value of the concave-convex height difference H is 400-600nm.

[0039] In the present invention, it should be understood that the double-screw extruder is based on the prior art device, and a concave-convex structure (which has a convex portion and a concave portion) is provided on the spiral surface. That is, other structures except the concave-convex structure are prior art, for example, it also has a double-screw mechanism, and the double-screw mechanisms are interlocked, which will not be described in detail here.

[0040] In the present invention, it can be understood that during the mixing and dispersion process, there is no coating film on the surface of the second particles (i.e., there is no continuous adhesion, only point adhesion or partial adhesion), and the coating film is only used to adhere and disperse the first nanoparticles on the surface of the second particles, and will not melt and cover the entire surface of the second particles. This is because if there is a coating film on the surface of the second particles, it will destroy the interface structure and prevent the first nanoparticles from coating the surface of the second particles.

[0041] In the present invention, “the size of the first nanoparticle is smaller than the size of the second particle” includes that the size of the first nanoparticle is smaller than the size of the second particle in the same order of magnitude or in different orders of magnitude.

[0042] In some embodiments, the first nanoparticle and the second particle are both nanometer-sized.

[0043] In some preferred embodiments, the size of the second particles is micrometer-sized. This preferred solution is more conducive to uniform dispersion of micrometer-sized particles.

[0044] In some preferred embodiments, the particle size distribution range of the second particles is 1-1000 μm, preferably 1-800 μm, more preferably 5-500 μm.

[0045] In some preferred embodiments, the particle size distribution range of the first nanoparticles is 1-900 nm, and preferably the average particle size is 200-500 nm.

[0046] In some preferred embodiments, the volume percentage of the second particles in the total amount of the first nanoparticles and the second particles is 50%-99%; the volume percentage of the coating film in the total amount of the first nanoparticles and the second particles is 10%-80%, preferably 25%-60%. Under this preferred solution, the content of each material is appropriate, which is more conducive to uniform dispersion.

[0047] In some preferred embodiments, the first nanoparticles include at least one of metal nanoparticles and inorganic non-metallic nanoparticles.

[0048] In some preferred embodiments, the second particles include at least one of metal particles and inorganic non-metal particles.

[0049] The metal nanoparticles, inorganic non-metal nanoparticles, metal particles, and inorganic non-metal particles can be selected from a wide range and can all be used in the present invention. For example, the metal nanoparticles and metal particles independently include but are not limited to Ti, Cu, Ni, TC 4 The inorganic non-metallic nanoparticles independently include but are not limited to SiC, TiO 2 、CNTs、Al 2 O 3 wait.

[0050] In some preferred embodiments, the coating film is a binder layer. The binder may be selected from a wide range of materials, such as stearic acid, resin, and polyvinyl alcohol (PVA).

[0051] The temperature of the mixed dispersion makes the coating film soften and have viscosity. Softening here means that at least 10%-80% of the coating film melts into a fluid with viscosity, which is conducive to uniformly dispersing and adhering the first coated nanoparticles to the surface of the second particles, and the first nanoparticles do not contact each other. At this time, the surface of the first nanoparticles is still coated with the binder fluid, which still serves the purpose of eliminating the electrostatic attraction between the first nanoparticles; and part of the binder fluid will flow between the first nanoparticles and the second particles to play a role in bonding and dispersion, so that the final nanoparticles have excellent dispersion properties.

[0052] In some preferred embodiments, the mixing and dispersing temperature is 10-500° C., preferably 250-500° C., more preferably 300-500° C. Mixing and dispersing at the preferred temperature causes the coating to melt appropriately, which is more conducive to the bonding and dispersion between the first nanoparticles and the second particles.

[0053] In some preferred embodiments, the mixing and dispersing time is 10-200 min, preferably 60-100 min. The mixing and dispersing under the preferred time is more conducive to the uniform and dense dispersion and bonding between the first nanoparticles and the second particles.

[0054] In some preferred embodiments, the dispersion method further comprises the step of forming the first coated nanoparticles:

[0055] (1) In an inert atmosphere, a binder for forming a coating film is introduced into the twin-screw extruder for operation, so that the binder adheres to the surface of the concave-convex structure;

[0056] (2) Introducing the first nanoparticles into the double-screw extruder of step (1), and performing mixing and coating under an inert atmosphere to form a coating film on the surface of the first nanoparticles.

[0057] More preferably, the operating conditions include: a temperature of 10-500° C., preferably 20-100° C., and a time of 10-120 min.

[0058] More preferably, the mixed coating conditions include: a temperature of 100-500°C, preferably 280-500°C, a time of 10-200min, preferably 10-100min, and further preferably 60-100min. In the preferred embodiment, the binder has a high and suitable viscosity, which is conducive to coating a layer of binder of suitable thickness on the surface of the first nanoparticles through moderate shear strain, thereby eliminating the electrostatic attraction between the first nanoparticles, and is more conducive to the dense dispersion of the first nanoparticles in the subsequent mixed dispersion. Under the same conditions, if the temperature is too high, it will lead to a decrease in viscosity and be unsuitable, which is not conducive to coating a layer of binder on the surface of the first nanoparticles. If the temperature is too low, the binder cannot be melted, and it is difficult to coat the surface of the first nanoparticles uniformly.

[0059] In the present invention, the inert atmosphere is provided by an inert gas, and the inert gas includes but is not limited to argon, nitrogen and the like.

[0060] The nanoparticles obtained by the dispersion method of the present invention are uniformly dispersed both macroscopically and microscopically, and the dispersed particles will not agglomerate over time; and can be recycled for multiple times, saving costs and eliminating waste.

[0061] In a second aspect, the present invention provides highly dispersed nanoparticles, which are prepared by the dispersion method described in the first aspect.

[0062] In the highly dispersed nanoparticles of the present invention, since the first nanoparticles and the second nanoparticles are evenly dispersed, the second particles do not contact each other, and the mutual electrostatic attraction is eliminated, there will be no agglomeration even if they are stored for a long time.

[0063] The highly dispersed nanoparticles of the present invention can be used in fields including but not limited to the preparation of composite materials, coatings, and the like.

[0064] In a third aspect, the present invention provides a particle-reinforced metal matrix composite material, which comprises the highly dispersed nanoparticles described in the second aspect, and an alloy; the performance of the particle-reinforced metal matrix composite material meets the following requirements: tensile strength is higher than 260MPa, yield strength is higher than 200MPa, and elongation is higher than 3%; preferably, the tensile strength is higher than 350MPa, the yield strength is higher than 300MPa, and the elongation is higher than 10%.

[0065] Preferably, the first nanoparticles and the alloy contain the same metal element, and the content of the metal element in the first nanoparticles is above 60-80%. For example, when the particle-reinforced metal matrix composite material is an aluminum-based composite material, the first nanoparticles are aluminum particles; when the particle-reinforced metal matrix composite material is a copper-based composite material, the first nanoparticles are copper particles.

[0066] The nanoparticles of the present invention can be prepared by compounding with any alloy (such as magnesium-based alloy) using any existing method (such as melt stirring method) to obtain the particle-reinforced metal-based composite material. The key to the present invention is to use the above-mentioned specific highly dispersed nanoparticles to reinforce the metal-based composite material.

[0067] The present invention is described in more detail below in conjunction with specific embodiments, wherein the concave-convex projections D in the following embodiments are all in the range of 0.1-0.5 mm, and the concave-convex height differences H are all in the range of 250-600 nm, but the respective average values ​​are different and are described in each embodiment.

[0068] Example 1

[0069] The double-screw extruder used in this embodiment has double helices that bite each other, and the surface of the spiral blade (i.e., the spiral surface) is rough and has a concave-convex structure: the average value of the concave-convex projection D is 0.25 mm, and the average value of the concave-convex height difference HH (i.e., the concave-convex height difference) is 500 nm.

[0070] The binder resin used in this embodiment is 10% of the volume fraction of the added powder (nano titanium particles with an average particle size of 300nm and magnesium powder with an average particle size of 10μm). The volume fraction of magnesium powder accounts for 90% of the powder. The specific dispersion method is as follows:

[0071] 1. First, put the resin into the double-screw extruder and run it at 80℃ for 20 minutes, and the spiral surface of the concave-convex structure is covered with resin;

[0072] 2. Then put the titanium nanoparticles into a double-screw extruder, protect it with argon gas, operate it at a temperature of 310°C for 20 minutes, so that the surface of the titanium nanoparticles is coated with a layer of resin;

[0073] 3. Magnesium powder particles and titanium nanoparticles coated with binder are placed in a double screw extruder, protected by argon, and operated at 310°C for 20 minutes. Titanium nanoparticles are evenly dispersed and distributed on the surface of magnesium powder particles without contact. Titanium nano-mixed particles are obtained, and their microscopic pictures are as follows: Figure 2 As shown in the figure, it can be seen that the nano-titanium particles in the highly dispersed particles are distributed on the surface of the magnesium powder, and the nano-titanium particles distributed on the surface of the magnesium powder do not contact each other.

[0074] 4. The titanium nanoparticles can be recycled multiple times after double-screw extrusion. There is a layer of resin film on the surface of titanium nanoparticles, and the nanoparticles are distributed on the surface of magnesium large particles. The nanoparticles distributed on the surface of large particles do not contact each other.

[0075] 5. The dispersed titanium nano-mixed particles are melt-stirred at a temperature above the liquidus temperature of the magnesium alloy phase diagram, about 650° C., and compounded with a magnesium-based alloy (grade: AZ31) to prepare a composite material.

[0076] The properties of the obtained composite material include: tensile strength higher than 350 MPa, yield strength higher than 300 MPa, and elongation higher than 10%.

[0077] Comparative Example 1

[0078] Titanium nanoparticles with an average particle size of 300 nm and magnesium powder with an average particle size of 10 μm (the amount used is the same as in Example 1) are uniformly mixed by ball milling to obtain mixed particles. Figure 3 As shown in the figure, it can be seen that the titanium nanoparticles have obvious agglomeration phenomenon on the surface of the magnesium ball and the distribution is very uneven.

[0079] The mixed particles were compounded with a magnesium-based alloy (with the same composition as in Example 1) using the same method as in Example 1 to prepare a composite material.

[0080] Nano-titanium particles are obviously embedded in the interface of magnesium particles, resulting in poor interface bonding. The tensile strength and cross-sectional elongation of the resulting composite material are significantly reduced, with the tensile strength being lower than 250 MPa, the yield strength being lower than 200 MPa, and the elongation being lower than 5%.

[0081] Comparative Example 2

[0082] Nano-titanium particles with an average particle size of 300 nm and magnesium powder with an average particle size of 10 μm were mixed and dispersed with a binder resin (the same as in Example 1) in a conventional twin-screw extruder (the spiral blade surface of which is not provided with a concave-convex structure), and operated at a working temperature of 310° C. for 20 min. The amounts of each raw material were the same as in Example 1. Then, a magnesium-based composite material was prepared by a melt stirring method (the conditions were the same as in Example 1).

[0083] In this comparative example, because the extruder ran for too long, the grains grew significantly, resulting in a significant decrease in the strength and toughness of the composite material obtained, with a tensile strength of less than 260 MPa, a yield strength of less than 250 MPa, and an elongation of less than 8%.

[0084] Example 2

[0085] This embodiment uses SiC nanoparticles with an average particle size of 400 nm and aluminum powder with an average particle size of 100 μm.

[0086] The double-screw extruder used in this embodiment has double helices interlocking with each other, and the surface of the spiral blade is rough and has a concave-convex structure: the average value of the concave-convex projection D is 0.25 mm, and the average value of the concave-convex height difference H is 500 nm;

[0087] The binder used in this embodiment is stearic acid, and its amount is the same as that in embodiment 1. The volume fraction of aluminum powder accounts for 90% of the powder.

[0088] The specific dispersion method is as follows:

[0089] 1. First, put stearic acid into the double-screw extruder and run it at 310℃ for 20 minutes. The surface of the concave-convex spiral surface is covered with stearic acid;

[0090] 2. Then put the nanoparticles into a double-screw extruder, protect with argon gas, operate at 400°C for 20 minutes, so that the surface of the nanoparticles is coated with a layer of stearic acid;

[0091] 3. The large aluminum powder particles and the SiC nanoparticles coated with a binder on the surface were placed in a double-screw extruder, protected by argon gas, and operated at a working temperature of 400°C for 20 minutes. The nanoparticles were evenly dispersed and distributed on the surface of the large aluminum powder particles without contacting each other. SiC nano-mixed particles were obtained. From the microscopic picture, it can be seen that the SiC nanoparticles in the highly dispersed particles are distributed on the surface of the aluminum powder, and the SiC nanoparticles distributed on the surface of the aluminum powder do not contact each other.

[0092] 4. The SiC nano-mixed particles after double-screw extrusion can be recycled multiple times. There is a layer of stearic acid film on the surface of SiC nano-particles, and the nano-particles are distributed on the surface of large aluminum powder particles. The nano-particles distributed on the surface of large particles do not contact each other.

[0093] 5. The dispersed nano-hybrid particles are compounded with aluminum-based alloy (grade 6025) by melt stirring method to prepare composite materials.

[0094] The obtained composite material has the following properties: tensile strength higher than 600 MPa, yield strength higher than 500 MPa, and elongation higher than 30%.

[0095] Example 3

[0096] The same procedure as in Example 1 is carried out, except that

[0097] Diamond nanoparticles with an average particle size of 300 nm are used to replace the titanium nanoparticles, copper powder with an average particle size of 200 μm is used to replace the magnesium powder, and the binder PVC is used to replace the resin. The working temperature in step 2 and step 3 is 450° C.; the rest is the same as in Example 1, to obtain diamond nano-mixed particles;

[0098] The diamond nano-mixed particles are compounded with a copper-based alloy (composed of brass) by a melt stirring method (same as in Example 1) to prepare a composite material.

[0099] The diamond nano-hybrid particles after double-screw extrusion can be recycled multiple times. There is a layer of PVC film on the surface of the diamond nano-particles, and the diamond nano-particles are distributed on the surface of the large copper particles. The nano-particles distributed on the surface of the large copper particles do not touch each other. From the microscopic picture of the diamond nano-hybrid particles, it can be seen that the highly dispersed diamond nano-hybrid particles are distributed on the surface of the copper powder, and the diamond nano-hybrid particles distributed on the surface of the copper powder do not touch each other.

[0100] The properties of the obtained composite material include: tensile strength higher than 300 MPa, yield strength higher than 200 MPa, and elongation higher than 40%.

[0101] Example 4

[0102] The process is carried out in accordance with Example 1, except that the concavo-convex structure of the twin-screw extruder is different, specifically, the average value of the concavo-convex projection D is 0.5 mm.

[0103] The properties of the obtained composite material include: tensile strength higher than 300 MPa, yield strength higher than 250 MPa, and elongation higher than 5%.

[0104] Example 5

[0105] The process is carried out in accordance with Example 1, except that the concavo-convex structure of the double-screw extruder is different. Specifically, the average value of the concavo-convex height difference H is 300 nm.

[0106] The performance of the composite material obtained is slightly inferior to that of Example 1: the tensile strength is higher than 280 MPa, the yield strength is higher than 230 MPa, and the elongation is higher than 4%.

[0107] Example 6

[0108] The process is carried out in accordance with Example 1, except that the working temperature in step 3 is 100°C.

[0109] The performance of the composite material obtained is slightly inferior to that of Example 1: the tensile strength is higher than 260 MPa, the yield strength is higher than 210 MPa, and the elongation is higher than 3%.

[0110] It can be seen from the above-mentioned Example 1 and Comparative Example 1 that the mixed particles obtained by using the embodiments of the present invention have better dispersibility and better performance when used in metal-based composite materials. It can be seen from Example 1 and Examples 4-5 that the preferred range of the concave-convex projection D and the concave-convex height difference H are suitable, which can significantly improve the toughness of the composite material. It can be seen from Example 1 and Example 6 that the preferred working temperature in step 3 is more conducive to the dispersion of the particles, thereby helping to enhance the performance of the obtained composite material.

[0111] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for dispersing nanoparticles, characterized in that: include: In a double-screw extruder, under an inert atmosphere, first coated nanoparticles and second particles are mixed and dispersed; the first coated nanoparticles include first nanoparticles and a coating film coated on the surface of the first nanoparticles; wherein the size of the first nanoparticle is smaller than the size of the second nanoparticle; The temperature of the mixed dispersion causes the coating film to soften and become viscous; The double-screw extruder has a spiral surface, and a concave-convex structure is arranged on the spiral surface, and the concave-convex structure satisfies: the concave-convex projection D is 0.1-0.5mm, and the concave-convex height difference H is 250-600nm. The concave-convex projection D refers to the projection distance of any convex part or any concave part in the concave-convex structure on the spiral surface under the irradiation of light perpendicular to the spiral surface, and the concave-convex height difference H refers to the distance between the highest point of any convex part and the lowest point of any concave part in the irradiation direction of light perpendicular to the spiral surface.

2. The dispersion method according to claim 1, characterized in that The size of the second particles is in the micron level.

3. The dispersion method according to claim 2, characterized in that The particle size distribution range of the second particles is 1-1000 μm.

4. The dispersion method according to claim 1, characterized in that The volume percentage of the second particles in the total amount of the first nanoparticles and the second particle raw materials is 50%-99%; the volume percentage of the coating film in the total amount of the first nanoparticles and the second particles is 10%-80%.

5. The dispersion method according to claim 1, characterized in that The first nanoparticles include at least one of metal nanoparticles and inorganic non-metallic nanoparticles; the second particles include at least one of metal particles and inorganic non-metallic particles; And / or, the coating film is a binder layer, comprising at least one of stearic acid, resin, and polyvinyl alcohol.

6. The dispersion method according to claim 1, characterized in that The mixing and dispersing temperature is 10-500° C., and / or the mixing and dispersing time is 10-200 min.

7. The dispersion method according to claim 6, characterized in that The mixing and dispersing temperature is 250-500°C.

8. The dispersion method according to claim 1, characterized in that The dispersion method further comprises the step of forming the first coated nanoparticles: (1) In an inert atmosphere, introducing a binder for forming a coating film into the twin-screw extruder and operating the device so that the binder adheres to the surface of the concave-convex structure; (2) Introducing the first nanoparticles into the double-screw extruder of step (1) for mixing and coating under an inert atmosphere.

9. The dispersion method according to claim 8, characterized in that The operating conditions include: temperature of 10-500° C. and time of 10-120 min.

10. The dispersion method according to claim 8, characterized in that The mixed coating conditions include: temperature of 100-500° C. and time of 10-200 min.

11. A highly dispersed nanoparticle, characterized in that: The invention is prepared by the dispersion method described in any one of claims 1 to 10.

12. A particle-reinforced metal matrix composite material, characterized in that: It comprises the highly dispersed nanoparticles as described in claim 11, and an alloy; the properties of the particle-reinforced metal matrix composite material meet the following requirements: tensile strength higher than 260 MPa, yield strength higher than 200 MPa, and elongation higher than 3%.

13. The particle-reinforced metal matrix composite material according to claim 12, characterized in that: The properties of the particle-reinforced metal matrix composite material meet the following requirements: tensile strength higher than 350 MPa, yield strength higher than 300 MPa, and elongation higher than 10%.